Faktor yang Memengaruhi Pemilihan Moda Transportasi pada Pengguna Bus Trans Jatim Koridor Mojokerto-Jombang - Mukhamad Khambali Ramadani; Ahmad Ridwan; Prima Eko Agustyawan (Jurnal Talenta Sipil, 2026)
Public transportation plays an important role in supporting community mobility and reducing dependence on private vehicles, particularly along the Mojokerto–Jombang corridor, which has relatively high travel intensity. However, the utilization of Trans Jatim Bus services along this corridor remains relatively low compared to private vehicles and other transportation modes. This study aims to analyze the factors influencing user preferences in transportation mode choice and to identify the most dominant attributes affecting the decision to use Trans Jatim Bus services. This research employed a quantitative method with a descriptive approach by distributing questionnaires to 97 respondents along the Mojokerto–Jombang corridor. The data were analyzed using binary logistic regression with the assistance of IBM SPSS Statistics 26. The results show that the regression model achieved a classification accuracy of 85.0% and a Nagelkerke R² value of 0.602, indicating that 60.2% of the variation in mode choice decisions can be explained by the variables included in the model. The Omnibus Test result showed a significance value of 0.000 (